Abnormal acrocentric Y chromosome in crossbreed cattle bulls - Youdhveer Singh; AS Yadav; SK Niranjan; B Prakash (Journal of Livestock Biodiversity, 2025)
Reproductive ef iciency is the most crucial issue faced by the dairy industries in India and abroad. A variety of factors affect the reproductive performance of farm animals. Chromosomal abnormalities cause a drop in reproductive performance or even complete infertility in the carrier animals. Present investigation was undertaken to detect chromosomal abnormality, if any, in 206 breeding bulls of exotic (Bos taurus, 2n=60), indigenous (Bos indicus, 2n=60) cattle breeds and crossbreeds maintained at Central Institute for Research on Cattle, Meerut and Animal Breeding Centre, Salon, Uttar Pradesh. Chromosomal preparations were made using standard blood lymphocyte culture from animals under study. At least 30 metaphase spreads were screened per animal to detect the chromosomal aberrations and prepare the karyotype. Giemsa staining of chromosome revealed that 98.06% cattle bulls possessed normal chromosome. However, 1.94% bulls showed abnormal Y chromosome complements in crossbreed bulls. Extensive use of breeding bulls in breeding programme through artificial insemination (AI) made it mandatory to screen for chromosomal anomalies before inclusion in breeding programme. It will not only check the quick spread of chromosomal abnormalities in animal population rather it will save the time and amount spent on rearing the abnormal animals. Various types of chromosomal anomalies have been reported in India but the frequency of chromosomal abnormalities is much less as compared to reported worldwide.